FOUNDATION DESIGN for a COMMERCIAL MALL in - NABLUS - عمر جمعه; انغام كيوان; ساجي الاحمد; جاسر قادوس (My University, 2023)
The main aim of this graduation project is to select and design the most suitable foundation system or systems of Saint Elias Hotel in Bethlehem, Beit sahour. The hotel has 12 floor and the average area of floors is 1200 m2. The main problem in designing foundations in general is the low bearing capacity of the soil it is standing on and the natural land surrounding it. The bearing capacity is estimated to be 50 KN/m2 (0.5 kg/cm2). In this project we studied Several possibilities for this foundation system in order to find the best system for this project that satisfies the requirements of the loads and the building itself while at the same time being the most economical many suggestions were studied in this project either to use deep foundation or perfuming soil improvement of the soil at the site. At the end a suitable foundation system will be selected and designed according to the standards. Foundation details (size, thickness, reinforcement, etc